2016
DOI: 10.15585/mmwr.mm6531a2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Neonatal Abstinence Syndrome — 28 States, 1999–2013

Abstract: Neonatal abstinence syndrome (NAS) is a postnatal drug withdrawal syndrome that occurs primarily among opioid-exposed infants shortly after birth, often manifested by central nervous system irritability, autonomic overreactivity, and gastrointestinal tract dysfunction (1). During 2000-2012, the incidence of NAS in the United States significantly increased (2,3). Several recent publications have provided national estimates of NAS (2,3); however, data describing incidence at the state level are limited. CDC exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
213
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 264 publications
(228 citation statements)
references
References 8 publications
(7 reference statements)
13
213
0
2
Order By: Relevance
“…Additionally, exposure may cause neonatal abstinence syndrome (NAS), in which the fetus develops symptoms of withdrawal following delivery (Kocherlakota, 2014; Stover and Davis, 2015). Since 1999, the incidence of NAS is estimated to have increased by over 300%, coinciding with the onset of today’s opioid epidemic (Ko et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, exposure may cause neonatal abstinence syndrome (NAS), in which the fetus develops symptoms of withdrawal following delivery (Kocherlakota, 2014; Stover and Davis, 2015). Since 1999, the incidence of NAS is estimated to have increased by over 300%, coinciding with the onset of today’s opioid epidemic (Ko et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In 2012 alone the syndrome was diagnosed in 21,732 infants in the United States. [1][2][3] From 2000 to 2012, the rate of NAS in the United States has increased by nearly 5-fold. 1,2 In a study examining 299 neonatal intensive care units (NICUs) in the United States from 2004 through 2013, the rate of NICU admissions for NAS increased from 0.7% to 2.7% of all admissions and made up 4% of all NICU days.…”
Section: Introductionmentioning
confidence: 99%
“…4 Previous research has shown that inpatient management using traditional strategies of care for infants with NAS led to a length of stay ranging from 8-105 days with a median of 25-34 days. [3][4][5] Oei et al 6 found that inpatient length of stay was decreased with the establishment of an outpatient clinic designed specifically for managing NAS patients.…”
Section: Introductionmentioning
confidence: 99%
“…The recent rise of opioid use in pregnancy and NAS has disproportionately occurred in rural areas (9, 10)** Using administrative data from 2004 to 2013, Villapiano et al(11)* found the incidence of NAS per 1000 hospital births increased from 1.2 to 7.5 among rural infants and from 1.4 to 4.8 among urban infants. The demographic differences between rural and urban areas is also apparent in state surveillance data.…”
Section: Changing Epidemiologymentioning
confidence: 99%
“…Ko et al (10)** detailed state-specific NAS incidence rates per 1,000 hospital births in 2013. They found NAS incidence of 0.7 in Hawaii contrasted by 33.4 in West Virginia.…”
Section: Changing Epidemiologymentioning
confidence: 99%